1990
DOI: 10.1161/01.atv.10.3.449
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor and occlusive arterial thrombosis. A study in normal and von Willebrand's disease pigs with diet-induced hypercholesterolemia and atherosclerosis.

Abstract: The thrombotic response of atherosclerotic arteries to stenosis and Injury was studied In 14 pigs, eight normal and six with von Willebrand's disease (vWD). Atherosclerosis was produced by feeding a 1% to 2% cholesterol diet for 24 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…In the pigs, protection against aortic atherosclerosis was found, whereas no protection was found in the coronary arteries. 8,24,31,32 It is known that the pace of development of atherosclerosis is different for the various sites in the vessel tree, depending on some recognized factors, such as shear stress, and some as yet unknown factors. 33 In the present study, we found advanced atherosclerotic lesions and found no differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the pigs, protection against aortic atherosclerosis was found, whereas no protection was found in the coronary arteries. 8,24,31,32 It is known that the pace of development of atherosclerosis is different for the various sites in the vessel tree, depending on some recognized factors, such as shear stress, and some as yet unknown factors. 33 In the present study, we found advanced atherosclerotic lesions and found no differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been reported that pigs with von Willebrand disease, similar to human type 3 von Willebrand disease (ie, no vWF antigen), are relatively protected against diet-induced atherosclerosis. 34,35 This finding has been attributed to the lack of vWF-mediated platelet adhesion to the subendothelium as an important contributing event to atherogenesis. In view of the findings on the sequestering and subsequent storage of P-selectin by multimeric vWF, we suggest that the protection from atherosclerosis in vWF-deficient pigs may be accounted for by the absence of vWF and the subsequent deficient availability of P-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…The Doppler crystal was energized by a range-gated pulsed Doppler unit. 12 The signal was range-gated to maximum clarity.…”
Section: Induction Of Ocdusive Arterial Thrombosismentioning
confidence: 99%
“…The protocol for the induction of arterial thrombosis has been fully described previously 12 and is briefly described here. Throughout the procedure, the Doppler signal was observed for cyclic flow reductions (CFRs) or permanent cessation of flow (PCF).…”
Section: Induction Of Ocdusive Arterial Thrombosismentioning
confidence: 99%